Implementation of Location Base Service Method Using WI-FI Network For Object Recognition at Museum - Rakhmania, Amalia Eka; Prasetyo, Junaedi Adi; Refiza, Rizky (Indonesian Society of Applied Science (ISAS), 2022)
The museum that is currently being built is used as a place to manage existing historical objects, because real historical objects are easy to know when in the museum. The current management of the museum still uses a manual system, where visitors come to the museum and then see the historical objects in the museum. Nowadays, with the rapid development of the times, the use of advances in information can be used whenever and wherever the user is. Location-based services in museums can be used to develop object recognition systems implemented in museums. In this research, a Location Base Service (LBS) system will be created that uses an android application that is connected to a server to make it easier to study historical objects. The android device will transmit the current position signal received by the Access Point. The Android application functions as a viewer of nearby historical object description objects. When the user wants to observe a nearby historical object, the user will display a video about the object to introduce nearby objects. To support the Location Base Service (LBS) system, several Access Points to track users via wireless connected to Android devices.